2016
DOI: 10.1038/cr.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide signals cell non-autonomous mitochondrial unfolded protein response

Abstract: Neurons have a central role in the systemic coordination of mitochondrial unfolded protein response (UPRmt) and the cell non-autonomous modulation of longevity. However, the mechanism by which the nervous system senses mitochondrial stress and communicates to the distal tissues to induce UPRmt remains unclear. Here we employ the tissue-specific CRISPR-Cas9 approach to disrupt mitochondrial function only in the nervous system of Caenorhabditis elegans, and reveal a cell non-autonomous induction of UPRmt in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
131
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 49 publications
6
131
2
Order By: Relevance
“…Flp-2 transcript levels are enhanced in the presence of neuronal mitochondrial stress, consistent with a role in the cell non-autonomous regulation of the UPR mt . Indeed, overexpression of FLP-2 specifically activates the UPR mt and not other stress responses (27). Together, these studies suggest that neuronal control of the UPR mt in distal tissues is likely complex involving the secretion of multiple mitokine signals.…”
Section: Caenorhabditis Elegansmentioning
confidence: 84%
See 1 more Smart Citation
“…Flp-2 transcript levels are enhanced in the presence of neuronal mitochondrial stress, consistent with a role in the cell non-autonomous regulation of the UPR mt . Indeed, overexpression of FLP-2 specifically activates the UPR mt and not other stress responses (27). Together, these studies suggest that neuronal control of the UPR mt in distal tissues is likely complex involving the secretion of multiple mitokine signals.…”
Section: Caenorhabditis Elegansmentioning
confidence: 84%
“…In the first study, the bioamine neurotransmitter serotonin was found to be required for activation of the UPR mt in the intestine as a consequence of mitochondrial protein aggregate accumulation in neurons (26). In a parallel study, interneuron secretion of the neuropeptide FLP-2 was necessary and sufficient for UPR mt activation in the intestine (27). Flp-2 transcript levels are enhanced in the presence of neuronal mitochondrial stress, consistent with a role in the cell non-autonomous regulation of the UPR mt .…”
Section: Caenorhabditis Elegansmentioning
confidence: 99%
“…While the relationship between FLP-2 and serotonin has not been examined, it is safe to assume that a number of interesting signaling events occur downstream of both molecules to affect the regulation of intestinal ATFS-1. Both studies indicate that ATFS-1 is essential in both the sensing neurons as well as in the intestinal cells for non-autonomous UPR mt activa-tion [3,5]. In neurons where mitochondria are perturbed directly, ATFS-1 activation is likely achieved by impaired mitochondrial protein import effi ciency.…”
mentioning
confidence: 99%
“…However, those cell types and the receptor remain to be identified as expression of FLP-2 specifically by intestinal cells was not sufficient to activate the intestinal UPR mt [5]. Thus, FLP-2 likely functions elsewhere.…”
mentioning
confidence: 99%
See 1 more Smart Citation